Does Input-Trade Liberalization Affect Firms' Foreign Technology Choice?. (10th December 2016) - Bas, Maria; Berthou, Antoine
Abstract: This paper studies the impact of input-trade liberalization on firms' decision to upgrade foreign technology embodied in imported capital goods. Our empirical analysis is motivated by a simple theoretical framework of endogenous technology adoption, heterogeneous firms and imported inputs. The model predicts a positive effect of input tariff reductions on firms' technology choice to source capital goods from abroad. This effect is heterogeneous across firms depending on their initial productivity level. Relying on India's trade liberalization episode in the early 1990s, we demonstrate that the probability of importing capital goods is higher for firms producing in industries that have experienced greater cuts on tariffs on intermediate goods. Only those firms in the middle range of the initial productivity distribution have benefited from input-trade liberalization to upgrade their technology.